Mucking Around the Marsh: Resiliency Techniques and Recommendations for Marshland Management. - Duprey, Alex; Frapaise, Laurent; Jameson, Danielle; Keimel, Annaliese; Rickley, Liz. (Tufts University. Tisch Library., 2020)
2020 M.A. in Urban and Environmental Policy and Planning Field Project. Client: Great Marsh Partnership.